2015
DOI: 10.1002/aoc.3265
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 8‐hydroxyquinolium chloroacetate and synthesis of complexes derived from 8‐hydroxyquinoline, and characterization, density functional theory and biological studies

Abstract: 8-Hydroxyquinolium chloroacetate (L 1 ) was synthesized and characterized. The results suggest that L 1 loses ethyl chloroacetate ion on coordination at low pH (2-5) and consequently it behaves as 8-hydoxyquinoline (L 2 ). Cu 2+ , Co 2+ , Pt 4+ , Pd 2+ , Au 3+ , Ag + and Nd 3+ complexes derived from L 2 have been synthesized and characterized using spectral, magnetic and thermal measurements. L 2 acts as a neutral bidentate ligand in the case of Cu 2+ , Co 2+ , Pt 4+ , Pd 2+ and Nd 3+ complexes and as a monone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…From Table 3, we are able to notice that there's an increase in the estimated binding energy of the complexes ( 2–12 ) compared with that of the hydrazone–oxime (H 2 L,1). This implies that the stability of the synthesized chelated compounds is larger than stability the hydrazone–oxime (H 2 L,1) 84 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From Table 3, we are able to notice that there's an increase in the estimated binding energy of the complexes ( 2–12 ) compared with that of the hydrazone–oxime (H 2 L,1). This implies that the stability of the synthesized chelated compounds is larger than stability the hydrazone–oxime (H 2 L,1) 84 …”
Section: Resultsmentioning
confidence: 99%
“…The charge of atoms play a significant role in the calculations of quantum chemical parameters for a molecular system because of the charge of atoms effect on the polarizability, electronic structure, vibrational spectra, dipole moment, and other molecular system properties. 85 The information attained by Mulliken analysis revealed that the hydrogen atoms charge are positive (1.533 Â 10 À1 -4.251 Â 10 À1 a.u. ), due to their losing of electrons to the adjacent carbon atoms, while H-13 and H-16 have the extreme positive charge than the other hydrogen atoms because of their attachment to the electronegative atom (O-12 and N-15).…”
Section: Mulliken Atomic Charges For the Hydrazone-oxime (H 2 L1)mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to retard (or eliminate) the negative influence of such water on the formation of supported single atoms, a chelating agent was introduced immediately following the precursor adsorption step. This chelating agent, 8-hydroxyquinoline (8-HQ), has a high affinity for transition metals (41)(42)(43)(44), and has been shown to adsorb on a variety of oxide and carbon surfaces for applications in metal extraction (45)(46)(47). We surmised that 8-HQ, which is not soluble in water, will isolate the metal precursor on the support surface without the need for defects or anchoring sites (Fig.…”
Section: One-sentence Summarymentioning
confidence: 99%
“…In order to retard (or eliminate) the negative influence of such water on the formation of supported single atoms, a chelating agent was introduced immediately following the precursor adsorption step. This chelating agent, 8-hydroxyquinoline (8-HQ), has a high affinity for transition metals (40)(41)(42)(43), and has been shown to adsorb on a variety of oxide and carbon surfaces for applications in metal extraction (44)(45)(46). We surmised that 8-HQ, which is not soluble in water, will isolate the metal precursor on the support surface without the need for defects or anchoring sites (Fig.…”
mentioning
confidence: 99%